Cavitation in Single-Vane Sewage Pumps - P. U. Thamsen; T. Bubelach; T. Pensler; P. Springer (International Journal of Rotating Machinery)
Chair fluidsystemdynamics at TU Berlin investigated the cavitation behavior of a full-size single-vane sewage pump. Single-vane pumps are used for raw sewage with high content of dirt and sediments in larger sewage pumping stations. Cavitation measurement was done by using standard NPSH3% and the more sensitive incipient cavitation NPSHIC. Also, vibration and noise where observed. Contrary to very low NPSH3% values, very high NPSHIC values were measured. In a second step, the impeller was modified with special cavitation bores to reduce the cavitation effects. The NPSH3% values increased with cavitation bores, which underlines that this value is not a sufficient criteria describing cavitation. Using the much more sensitive NPSHIC, a significant reduction was obtained. Moreover, the cavitation formation was changed from a relative concentrated cloud to a distributed bubble form, which is much less aggressive in view of noise and erosion. Operational behavior improved with cavitation bores, noise and vibration levels especially came down to acceptable level. Practical experience demonstrates also avoidance of cavitation erosion.